Pembiasaan Berbahasa Daerah Madura (Bahasa Halus), Dalam Upaya Pelestarian Budaya Dan Penanaman Pendidikan Karakter Di Madrasah Ibtidaiyyah di Bangkalan Madura - Umi Musya'adah (Tarunateach: Journal of Elementary School, 2023)
Schools, in this case Madrasah Ibtidaiyyah, have a very important role in preserving culture and instilling character education from an early age in children. This role is very significant in changing good habits from an early age to children at Madrasah Ibtidaiyyah. In this 4.0 era, which is called the industrial revolution, many Indonesian children today use Indonesian more in their daily lives, and rarely use regional languages, many think that regional languages ​​are not cool or cheesy. Many parents are also starting to get used to only speaking Indonesian. Not only that, many children today also don't know the soft language of their region. In fact, speaking a soft regional language reflects good behavior or character in everyday life. How to speak has a big influence on a person's behavior and habits. Therefore, this article will discuss: understanding Madura regional language, the role of Madrasah Ibtidaiyyah in preserving Madura regional language, getting used to soft regional language from an early age, character education using soft language